In Vitro Reporter Assays for Screening of Chemicals That Disrupt Androgen Signaling - Gargi Bagchi Bhattacharjee; S. M. Paul Khurana (Journal of Toxicology)
Endocrine disruptive chemicals (EDCs) modulate hormone signaling and cause developmental and reproductive anomalies. Today, there is a global concern regarding endocrine disruption effects, particularly those mediated by the androgen receptor (AR). Androgen or male hormones are critical for the development and maintenance of male characteristics and numerous EDCs exist in the environment with the potential to disrupt androgen action. The threat is more during critical developmental windows when there is increased sensitivity to these compounds. Timely screening and detection of the EDCs is essential to minimize deleterious effects produced by these toxic chemicals. As a first line of screening, in vitro transcription assays are very useful due to their speed, convenience, and cost effectiveness. In this paper, recent in vitro reporter assays for detecting androgenic or antiandrogenic activity of EDCs have been reviewed. Two important cell systems used for this purpose, namely, the mammalian or yeast cell systems, have been discussed. Use of reporter genes such as bacterial luciferase (lux) and green fluorescent protein (gfp) has significantly improved speed and sensitivity of detection. Also, many of the current reporter assay systems can be used in a high throughput format allowing speedy evaluation of multiple potential EDCs at a lower price.